Discussion of the progress of history, apocalypticism, rebirth, and the immortality of the soul in Hinduism, Buddhism, and Judaism - Hermanni, Friedrich 1958- (2002)
People can save themselves only on their own, by their own power. We can, to be sure, presuppose a God; but what is this God and where does he live? If we regard him as a power, where does this power originate? Salvation in the sense of nirvana exists only in the midst of life and death. Buddha or God exists only in our power. In Buddhism, one must hold two perspectives in view. Becoming a Buddha is one of them. This is the final objective, the ideal, towards which one strives. The other is that the human being is a finite, imperfect being; therefore he must work hard to attain this objective. One can at every moment of his actions experience nirvana, contentedness, and still remain a finite being. (Arifuku)